Effect of Adsorption, Dispersion and Slug Size on Chemical EOR. - El-Khatib, Noaman A.F. (2010)
Analytical solutions for the diffusion equation for the case of a finite slug injection are derived considering adsorption and dispersion. It was found that the adsorption constant can be combined with the injected pore volume and the slug volume resulting in a modified definition of these dimensionless volumes. Solutions in terms of the error function are obtained. The principle of superposition is applied to account for the Finite slug injection. The effects of adsorption, dispersion and slug size on concentration profiles in the reservoir are investigated. The effluent concentration has a maximum value which depends on the reduced slug volume which incorporates the adsorption and the Peclet number which accounts for dispersion. The objective is to have the maximum effluent concentration above a specified critical concentration that is required to achieve the function of the injected chemical and to determine the minimum slug size that achieves this objective. The minimum reduced slug size will depend on the critical concentration and the Peclet number. The actual slug size will then depend on the adsorption coefficient.